Upaya Meningkatkan Kemampuan Guru Mengelola Pembelajaran Berbasis ICT - Betty Herawati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This study aims to describe efforts to improve teachers' ability to manage ICT-based learning. data collection tools using interviews, documentation, observation and literature review. Data analysis used descriptive qualitative analysis. Teachers are currently required to have the ability to carry out ICT-based learning. The obstacles faced by teachers in developing ICT-based learning include: the diverse conditions of students and factors of teaching experience, ability to operate learning media; the availability of school facilities is for teachers in implementing ICT-based learning. Teachers must be able to utilize information from the internet as well as teacher discussion forums as an effort to overcome problems in the preparation of a new ICT-based learning paradigm.